A Phenomenological Research of the Lived Experiences of Runaway Girls Who Live in Correction and Rehabilitation Centre in Tehran about Subjective Experiences - Maryam Falahatpishe; Mojtaba Habibi; Mansoureh Sadat Sadeghi; Mahmood Shamshiri (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: According to the high prevalence of running away from home by the teenager girls in Iran and the negative consequences of this issue in the society, this study aimed to investigate the phenomenon of running away from home by studying the lived experience about subjective experiences in girls who had been referred to correction and rehabilitation center in Tehran. Materials and Methods: 12 girls were chosen based on data saturation and they were interviewed by semi-structured interviews. The data were analyzed by interpretative phenomenology and Van Manen approach. Finally 5 main Themes were achieved. Results: The thematic analysis resulted in three sub-themes for subjective experiences including entanglement in negative emotions, being dehumanized, and feminine identity. Conclusion: The results emphasize the need for assessment of experiencing the negative emotions, being dehumanized, and identity crisis as the risk factors of running in teenagers to prevent the possibility of running away from home by teenagers.